2008
DOI: 10.1007/s11869-008-0021-z
|View full text |Cite
|
Sign up to set email alerts
|

The study of TSP and PM10 concentration and their heavy metal content in central area of Tehran, Iran

Abstract: Atmospheric particulate matter may exert serious health hazards because of its chemical characteristics. The main objective of this study is to assess the concentrations of total suspended particles (TSP), particulate matter (PM) with an aerodynamic diameter ≤10 μm (PM 10 ), and airtransmitted particulate trace metals in Tehran University (a central location in Tehran, capital of Iran) ambient air, for the period of 5 months viz. February-June 2007. Furthermore, the present work examines the daily levels of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 11 publications
2
29
0
2
Order By: Relevance
“…The study of particulate matter (PM) as air pollutant is important because of its effects on human health, atmospheric visibility, climate change, etc. [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The study of particulate matter (PM) as air pollutant is important because of its effects on human health, atmospheric visibility, climate change, etc. [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals associated with respirable particles have also been shown to increase lung or cardiopulmonary injuries caused by particulate air pollutant exposure (Espinosa et al, 2001;Cancio et al, 2008;Leili et al, 2008). Natural emissions (crustal minerals, forest fires and oceans), traffic and industrial emissions (combustion of fossil fuel and industrial metallurgical processes) are the principal sources of heavy metals in the ambient air (Park et al, 2008;Xu et al, 2010;Cheung et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the PM10 concentrations which exceeded the AAQS were caused by coal consumption from industry and vehicle transportation, road dust, dust from city construction projects, fireworks during celebrations, and dust storm (26,(32)(33)(34)(35).…”
Section: Resultsmentioning
confidence: 99%